Reconstructing mathematical success in post-pandemic learning environments: An intensive single-case study using grounded theory coding techniques - Wahyuningrum, Endang; Sudirman, Sudirman; Rodríguez-Nieto, Camilo Andrés (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to examine how successful mathematics learning is constructed through the dynamic interaction of affective dispositions, cognitive-metacognitive strategies, socio-pedagogical scaffolding, resilience, and epistemological flexibility within post-pandemic online learning environments. Method: An intensive single-case study design was employed, utilizing in-depth interviews with a student and three mathematics teachers as the primary data collection instrument. Data were systematically analyzed through open, axial, and selective coding procedures adapted from grounded theory. Findings: Four interrelated conceptual models emerged from the analysis: (1) the Ecosystemic Formation of Sustainable Learning Identity, (2) the Adaptive Academic Reconstitution Model, (3) Learning Ecosystem Support as an Adaptive Developmental System, and (4) the Adaptive Transitional Learning Ecosystem Model. Collectively, these models reconceptualize mathematical success not as a discrete performance outcome, but as an ecosystemic and developmentally sequenced achievement requiring coherent integration of internal identity formation, strategic regulatory capacity, and adaptive ecosystem support. Significance: These findings carry substantial implications for the development of post-pandemic pedagogical frameworks, advocating for holistic and identity-constitutive approaches that extend beyond mere content remediation in online mathematics education.